Students’ Perception On Non-Digital Game-Based Student Worksheet (ND-GBSW) for English Learning at SMP Negeri 1 Gerokgak - Amelia Margaratna Putri; Ni Luh Putu Eka Sulistia Dewi; Ni Putu Astiti Pratiwi (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study aimed to investigate the students’ perceptions of the Non-Digital Game-Based Student Worksheet (ND-GBSW) strategy in English learning implemented by an English teacher at SMP Negeri 1 Gerokgak. This study applied Basic Interpretative Study that involved interview data collection as the primary data, and complemented by survey data collection as the secondary data. The instruments were developed based on the perception theories by Qiong (2017) and Robbins & Judge (2013). The participants were the 8B class students who had experienced the implementation of ND-GBSW with the Finding a Treasure game under Narrative Text topic. Only three students were chosen to participate in the interview phase based on the high, medium, and low score in the questionnaire phase. The quantitative data were analyzed using descriptive statistics, while qualitative data using Thematic Analysis. The findings showed that 8B class students generally perceived ND-GBSW with the Finding a Treasure game as an engaging activity that supported their English learning process and encouraged their collaborative skills. Several challenges occurred, particularly regarding the challenge level of the game activity and the clarity of the worksheet instructions.